The IS auditor: what are the key knowledge requirements. (1st January 2013) - Seeburn, Kris
The increasing dependence on information systems (IS) by many businesses has resulted in concerns regarding auditing. The IS auditing landscape has changed from auditing 'around the box' to a hands-on approach (auditing through and within the box). Technology has and is changing very rapidly and so is the need for the IS audit profession to evolve and adapt. IS auditing is dependent on information technology (IT), it is essential that the IS auditor possess IT and auditing knowledge to bridge the gap between the IT and auditing professions. It is quintessential that both the information systems and the financial reporting aspect agree with each other to be delivered as an integral audit system. This paper aims at defining the key knowledge areas required for the IS auditing profession today.